2005
DOI: 10.1177/1545109706286555
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Psychological Morbidity in HIV-Infected and HIV-Uninfected Pregnant Women Using Community Counselors in Zimbabwe

Abstract: There is a high burden of psychological morbidity among pregnant women in Zimbabwe. Mental health services should be integrated into antenatal care to improve psychological health for all women in Zimbabwe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Eighteen publications from studies conducted in Zimbabwe [16, 17], Angola [18], Zambia [19], South Africa [20–28], Tanzania [2931], Kenya [32] and Nigeria [33] met the review eligibility criteria. Fifteen of these 18 publications reported on depressive symptoms or other mental health-related outcomes such as distress, anxiety or coping mechanisms [1622, 2532], two studies focused on IPV and pregnant HIV+ women [23, 33] and one study examined substance abuse in pregnant HIV+ women [24].…”
Section: Low-income Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen publications from studies conducted in Zimbabwe [16, 17], Angola [18], Zambia [19], South Africa [20–28], Tanzania [2931], Kenya [32] and Nigeria [33] met the review eligibility criteria. Fifteen of these 18 publications reported on depressive symptoms or other mental health-related outcomes such as distress, anxiety or coping mechanisms [1622, 2532], two studies focused on IPV and pregnant HIV+ women [23, 33] and one study examined substance abuse in pregnant HIV+ women [24].…”
Section: Low-income Countriesmentioning
confidence: 99%
“…Fifteen of these 18 publications reported on depressive symptoms or other mental health-related outcomes such as distress, anxiety or coping mechanisms [1622, 2532], two studies focused on IPV and pregnant HIV+ women [23, 33] and one study examined substance abuse in pregnant HIV+ women [24]. Four of these studies were clinical trials which evaluated interventions designed to improve mental health outcomes in pregnant HIV+ women.…”
Section: Low-income Countriesmentioning
confidence: 99%
“…22 In a recent study conducted at our site, the prevalence of psychological morbidity among pregnant women attending an urban primary care clinic was 17%. 23 Depression was the most frequent illness among women with psychological morbidity; 79% of women were evaluated by the psychiatrist and met the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria for clinical depression. 23 Studies have shown that depressive symptoms increase the risk of HIV disease progression and mortality among pregnant women, suboptimal compliance to antiretroviral therapy, and poor use of antenatal care.…”
Section: Journal Of Women's Healthmentioning
confidence: 99%
“…23 Depression was the most frequent illness among women with psychological morbidity; 79% of women were evaluated by the psychiatrist and met the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria for clinical depression. 23 Studies have shown that depressive symptoms increase the risk of HIV disease progression and mortality among pregnant women, suboptimal compliance to antiretroviral therapy, and poor use of antenatal care. 6,18,24,25 The objective of this study is to determine the risk factors associated with PND in a cohort of HIV-infected and HIV uninfected women who came for postpartum follow-up to two urban antenatal clinics in Zimbabwe.…”
Section: Journal Of Women's Healthmentioning
confidence: 99%
“…The acceptance rate of VCT among our ANC clients has been low, ranging from 20% to 63%. 6,8 Several reasons may account for poor antenatal VCT uptake among women in subSaharan Africa, including absence of prenatal care, fear of stigma and inadequate counselling experiences. [9][10][11] Thus innovative approaches to antenatal HIV testing are urgently required.…”
Section: Introductionmentioning
confidence: 99%